2014
DOI: 10.7150/ijbs.9997
|View full text |Cite
|
Sign up to set email alerts
|

The Prostate Basal Cell (BC) Heterogeneity and the p63-Positive BC Differentiation Spectrum in Mice

Abstract: The prostate epithelium is composed of basal (BC), luminal (LEC), and neuroendocrine (NEC) cells. It is unclear how many subtypes of BCs in the prostate and which subtype of BCs contains the main stem cell niche in the adult prostate. Here we report seven BC subpopulations according to their p63, cytokeratin 14 (K14) and K5 expression patterns, including p63-positive/K14-negative/K5-negative (p63+/K14-/K5-), p63-/K14+/K5-, p63-/K14-/K5+, p63+/K14+/K5-, p63+/K14-/K5+, p63-/K14+/K5+, and p63+/K14+/K5+ BCs. We ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 22 publications
3
54
0
Order By: Relevance
“…1B showed that prostaspheres are derived from the Nkx3.1 lineage. Lineage tracing also demonstrates that both basal and luminal cells in mouse prostate are derived from the cells that express P63 (20). Therefore, both basal and luminal cells are derived from the lineage.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…1B showed that prostaspheres are derived from the Nkx3.1 lineage. Lineage tracing also demonstrates that both basal and luminal cells in mouse prostate are derived from the cells that express P63 (20). Therefore, both basal and luminal cells are derived from the lineage.…”
Section: Discussionmentioning
confidence: 88%
“…However, it has been reported that P63, a basal cell marker, is required for prostate epithelial lineage commitment and prostate development (5,31). Recent reports with P63 CreERT2 lineage tracing reveal that both luminal and basal cells are derived from P63-expressing cells (20,24 CreERT2 -mediated activation of reporter genes demonstrates that both basal and luminal compartments contain P-SCs. Both luminal and basal P-SCs give rise to multiple lineages of cells either in a tumor microenvironment or coimplanted with urogenital mesenchymal cells.…”
Section: Discussionmentioning
confidence: 99%
“…R26 tdTomato , R26 LacZ , R26 rtTA mice were purchased from the Jackson Laboratory. p63-CreER mice were kindly provided by Dr. Jianmin Xu of Baylor College of Medicine 30 . The otet-CDX2-T2A-mCherry transgenic line was generated by pronuclear injection of linearized DNA.…”
Section: Methodsmentioning
confidence: 99%
“…Notably, androgen deprivation by castration results in significant epithelial cell death in the prostate, whereas subsequent testosterone supplementation results in rapid tissue regeneration. During androgen-mediated regeneration, luminal castration-resistant Nkx3.1-expressing cells (CARNs) as well as basal cell populations can display bipotency and self-renewal indicative of stem cell activity (Lee et al, 2014;Wang et al, 2009Wang et al, , 2013bWang et al, , 2015. Furthermore, during tissue damage and repair, such as in mouse models of prostatitis or luminal-specific anoikis, basal cells show significant capability to replace lost luminal cells Toivanen et al, 2016).…”
Section: Box 1 Prostate Gland Homeostasis and Regenerationmentioning
confidence: 99%